2015
DOI: 10.1080/20786190.2014.977066
|View full text |Cite
|
Sign up to set email alerts
|

Conditions frequently self-treated with herbal remedies by patients visiting a tertiary hospital in Gauteng, South Africa

Abstract: Background: Herbal medications are used worldwide for a variety of diseases and conditions. Patients often elect not to disclose their herbal use history, or health care practitioners fail to enquire about specific alternative therapy. The aim of this study was to assess the conditions most frequently self-treated with herbal remedies by patients visiting a tertiary hospital in Garankuwa, South Africa. Methods: Patients attending an out-patient's clinic at the Dr George Mukhari Academic Hospital were given a q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 18 publications
2
8
0
Order By: Relevance
“…For instance, a Nigerian study among inpatient and outpatients reported that 72% of the 200 outpatients are currently using TCAM products, whereas 18.5% of the 65 inpatients are reportedly using TCAM products. 153 Similar findings among outpatients were reported in similar studies in Nigeria (89.9%) 30 and South Africa (60.9%) 154 and among inpatients in Nigeria (14.2%) 155 and Uganda(18.3%). 156 …”
Section: Resultssupporting
confidence: 84%
“…For instance, a Nigerian study among inpatient and outpatients reported that 72% of the 200 outpatients are currently using TCAM products, whereas 18.5% of the 65 inpatients are reportedly using TCAM products. 153 Similar findings among outpatients were reported in similar studies in Nigeria (89.9%) 30 and South Africa (60.9%) 154 and among inpatients in Nigeria (14.2%) 155 and Uganda(18.3%). 156 …”
Section: Resultssupporting
confidence: 84%
“…For instance, a Nigerian study among inpatient and outpatients reported that 72% of the 200 outpatients are currently using TCAM products, whereas 18.5% of the 65 inpatients are reportedly using TCAM products. 153 Similar findings among outpatients were reported in similar studies in Nigeria (89.9%) 30 and South Africa (60.9%) 154 and among inpatients in Nigeria (14.2%) 155 and Uganda(18.3%). 156 Student population, healthcare professionals and academic staff The reviewed literature indicates that 38.4% of high school students in Nigeria used a TCAM product 157 compared with 81.8% and 75.1% TCAM product utilisation rates that were reported among Nigerian university students 31 and university students and staff, 158 respectively.…”
Section: General Inpatients and Outpatientssupporting
confidence: 84%
“…The prevalence of THM use observed in this study falls within the range, 6.1%–38.5%, documented in the systematic review of THM/CAM use in South Africa conducted by Peltzer [ 33 ]. This is however lower than what has been reported in other South African studies [ 20 , 26 ] and in studies conducted in different settings and countries within Africa such as in Nigeria [ 34 ], Ghana [ 35 ], and Uganda [ 36 ], and further afield in Korea [ 37 ], Turkey [ 38 ], Finland [ 39 ], and Australia [ 40 ]. The observed difference in prevalence of THM use might be as a result of variation in sample characteristics, study setting, and population.…”
Section: Discussionmentioning
confidence: 62%